Abordagem das noções iniciais de probabilidade em uma perspectiva construtivista - Cabral Junior, Rubens de Souza (2009)
The research had as objective to check what are the contributions and difficulties of teachers in planning and developing a hypothetical learning trajectory (HLT) about basic knowledge of probability for high school students. The justification of our research agrees with Simon s statement (1995) that there are a lot of researches in the area of learning with constructivists approach, but very little of their results are incorporated in the classes of teachers. Initially, we did a bibliographic review of the works whose theme is the process of teaching and learning of probability. From these results we made a sequence of teaching probability which we show for three teachers develop with their students, being on tenterhooks to consider the HLT and, at the same time, create new hypotheses about the process of teaching and learning of probabilities. The research shows that teachers who took part in the study have knowledge about the Laplace s approach in introduction of the concept of probability, however they need theoretical support about the possibility of learning basic knowledge of probability using the differences of frequentist and Laplace focus. This fact limited their contributions in the elaboration and development of HLT, leading teachers to a more contemplative than criticism attitude in relation to activities presented